Tissue-wide integration of mechanical cues promotes effective auxin patterning - Ramos, João R. D.; Maizel, Alexis; Alim, Karen (The European physical journal. Plus, 2021)
New plant organs form by local accumulation of auxin, which is transported by PIN proteins that localize following mechanical stresses. As auxin itself modifies tissue mechanics, a feedback loop between tissue mechanics and auxin patterning unfolds—yet the impact of tissue-wide mechanical coupling on auxin pattern emergence remains unclear. Here, we use a model composed of a vertex model for plant tissue mechanics and a compartment model for auxin transport to explore the collective mechanical response of the tissue to auxin patterns and how it feeds back onto auxin transport. We compare a model accounting for a tissue-wide mechanical integration to a model that regards cells as mechanically isolated. We show that tissue-wide mechanical coupling not only leads to more focused auxin spots via stress redistribution, but that it also mitigates the disruption to patterning when considering noise in the mechanical properties of each cell of the tissue. We find that this mechanism predicts that a local turgor increase correlates with auxin concentration, and yet auxin spots can exist regardless of the exact local turgor distribution.